TINDAKAN SUCTION TERHADAP BERSIHAN JALAN NAFAS PADA PASIEN INTRACEREBRAL HEMORRHAGE POST OP CRANIOTOMY : STUDI KASUS - Nonok Karlina; Fauziyatu Alfiyah, Suci; Nurcahyana, Yayan; Budihartiningrum, Fitriani; Prihatini, Nur (LPPM ITEKES Mahardika, 2023)
Intracerebral hemorrhage (ICH) is the deadliest type of stroke in the world that causes rupture of blood vessels so that patients experience a decrease in consciousness. Patients with decreased consciousness do not have an effective cough reflex resulting in a buildup of secrets in the airway. Suction is the main implementation for patients who are unable to remove secretions on airway hygiene. This case study aims to explain nursing care for Intracerebral Hemorrhage (ICH) patients in the ICU Room of Gunung Jati Hospital Cirebon. The type of research used is a case study approach. The study was conducted for 3 days. The results obtained based on patient assessment data experienced a buildup of sputum production in the airway. Nursing actions that can be given are suction actions. After 3 consecutive days, the patient's airway clearance increased. Nursing action of mucus sucking / suction is one of the effective interventions used in improving the airway of patients, especially in Intracerebral Hemorrhage (ICH) patients.